Association of Plasma Homocysteine Level and Carotid Intima-Media Thickness in Rheumatoid Arthritis Patients Receiving Methotrexate - Emrullah HAYTA; Sami HİZMETLİ and Mehmet Haydar ATALAR and Ziynet ÇINAR (Archives of Rheumatology, 2015)
Objectives: This study aims to evaluate the relationship between serum homocysteine levels and atherosclerotic plaques in carotid arteries in female patients with rheumatoid arthritis (RA). Patients and methods: Fifty-eight females with RA (mean age 45.50±11.69 years; range 42 to 60 years) and 22 female controls (mean age 47.3±8.9 years; range 38 to 62 years) with mechanical low back pain were included in the study. RA patients were divided into two groups: patients who were under methotrexate (MTX) therapy at least for two years (MTX group, n=32), and patients who did not receive MTX at least for past two years (non- MTX-disease-modifying antirheumatic drug group, n=26). RA patients’ disease activity scores in 28 joints were calculated. Carotid intima-media thickness and presence of atherosclerotic plaque were evaluated by high-resolution B-mode ultrasonography. Results: Plasma homocysteine levels were higher in MTX and non-MTX-disease-modifying antirheumatic drug groups compared to controls (16.88±6.84 and 10.37±2.54 μmol/L, respectively) and the difference was statistically significant (p=0.001). In MTX, non-MTX-disease-modifying antirheumatic drug and control groups, atherosclerotic plaque was detected in 11 (34.5%) and four (15.4%) patients, and one patient (4.5%), respectively. Carotid intima-media thickness was significantly higher in MTX group compared to other two groups and the difference was statistically significant (p=0.002). Pearson correlation analysis revealed a significant correlation between intima-media thickness and homocysteine levels in MTX group (r=0.49, p=0.006). Conclusion: According to our study results, methotrexate treatment in female patients with RA increases plasma homocysteine levels and prevalence of atherosclerotic plaque. High homocysteine levels in these patients may be a cause of atherosclerosis.